Healthcare providers and caregivers' perspectives on factors responsible for persistent malnutrition of under 5 children in Buhweju district, South Western Uganda; a phenomenological qualitative study - Catherine N. Abaasa; Godfrey Zari Rukundo; Savino Ayesiga; Susan Pearl Atukunda; Susan Campisi; Shawna O'Hearn; Noni MacDonald (BMC, 2021)
Abstract Background Unacceptably high levels of childhood malnutrition have been registered in all regions of Uganda over the years. Buhweju district alone contributed 46% prevalence of childhood malnutrition to the 47.8% estimated national prevalence for the whole of western Uganda in 2014. This study assessed health provider and caregiver opinions on factors responsible for persistent malnutrition among under five children in Engaju and Nyakishana sub counties. Methods In this phenomenological qualitative study, we conducted two key informant interviews and six focus group discussions with Village Health Team members and care takers of under five children in Engaju and Nyakishana sub-counties respectively.to explore their opinions on the factors responsible for persistent malnutrition in Buhweju District in May 2018. Data were thematically analyzed manually and using Atals Ti 7.5. Results Historical and geographical challenges, poverty and economic occupation, parental alcoholism and domestic violence as well as inadequate childcare services were identified as factors responsible for persistent malnutrition among under five children in Engaju and Nyakishana sub counties. Conclusion Persistent malnutrition in under five children is mainly due to historical and geographical challenges and its associated factors that include poverty and economic occupation, parental alcoholism and domestic violence and inadequate childcare services. Thus literacy education for mothers and young adolescent boys and girls through engaging local leaders, local nongovernmental organizations and Companies operating in the district to contribute to social services provision would limit the domestic violence and increase sensitization on male responsibilities in the children care in Buhweju district.